Magnetic Resonance Imaging in the Assessment of the Risk of Sudden Death in Cardiac Sarcoidosis: What Is Extensive or Significant Late Gadolinium Enhancement? - Pöyhönen,Pauli; Lehtonen, Jukka; Syväranta, Suvi; Velikanova, Diana; Mälkönen, Henriikka; Simonen, Piia; Nordenswan, Hanna-Kaisa; Uusitalo, Valtteri; Vihinen, Tapani; Kaikkonen, Kari; Haataja, Petri; Kerola, Tuomas; et al. (Wolters Kluwer Health, 2025)
Background:Cardiac sarcoidosis involves a significant but difficult-to-define risk of sudden cardiac death (SCD). Current guidelines recommend consideration of an implantable cardioverter defibrillator for patients with extensive or significant myocardial late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging. However, extensive/significant LGE is not defined.
Methods:A nationwide cardiac sarcoidosis registry was screened for patients entered before 2020 with cardiac magnetic resonance imaging done before or <3 months after diagnosis. Available studies were re-analyzed for LGE mass as a percentage of left ventricular (LV) mass and the number of LGE-positive LV segments in a 17-segment model. The occurrence of fatal or aborted SCD and ventricular tachycardia (VT) prompting therapy was recorded until the end of 2020 and subjected to cumulative incidence analyses, including competing events (LV assist device implantations, heart transplantations, and fatalities other than SCD). The predictors of SCD/VT were assessed using Fine and Gray modeling and time-dependent receiver operating characteristic analysis.
Results:Altogether, 305 patients (66% women, median age 51) with clinically manifest, definite (45%) or probable cardiac sarcoidosis (55%) were analyzed. On follow-up (median, 4.0 years), 21 SCDs, 60 VTs, and 14 competing events were noted. Both LGE mass and the number of LGE segments predicted the composite of SCD/VT (P<0.001), with receiver operating characteristic analyses identifying LGE mass ≥9.9% and ≥6 LGE segments as discriminative thresholds. At presentation, 70 patients were free of class I and class IIa implantable cardioverter defibrillator indications unrelated to LGE. Their 5-year rate of SCD/VT was 6.3% (0.0–14.8%) with LGE mass <9.9% versus 21.5% (6.5–36.6%) with higher LGE mass, and 6.9% (0.0–16.3%) with <6 LGE segments versus 20.5% (5.9–35.2%) with ≥6 segments.
Conclusions:In cardiac sarcoidosis, myocardial LGE making up ≥9.9% of LV mass or affecting ≥6 LV segments may suggest prognostically significant LV involvement and a high risk of SCD. However, prospective validation of the thresholds is needed.